Gas Infrastructure. Gas installation pipework with an operating pressure greater than 0, 5 bar for industrial installations and greater than 5 bar for industrial and non-industrial installations. Detailed functional requirements for design, materials, construction, inspection and testing Part 1, (7th March 2023) - British Standards Institution,
No abstract available